Aldehyde dehydrogenase 2 has cardioprotective effects on myocardial ischaemia/reperfusion injury via suppressing mitophagy - Wenqing eJi; Yuguo eChen; Shujian eWei; Panpan eHao; Junhui eXing (Frontiers Media S.A., 2016)
Mitophagy, a selective form of autophagy, is excessively activated in myocardial ischemia/reperfusion (I/R). The study investigated whether aldehyde dehydrogenase (ALDH2) exerted its cardioprotective effect by regulating mitophagy. Myocardial infarct size and apoptosis after I/R in rats were ameliorated by Alda-1, an ALDH2 activator, and aggravated by ALDH2 inhibition. Both in I/R rats and hypoxia/reoxygenation H9C2 cells, ALDH2 activation suppressed phosphatase and tensin homolog-induced putative kinase 1 (PINK1)/Parkin expression, regulating mitophagy, by preventing 4-hydroxynonenal and reactive oxygen species accumulation. Furthermore, the effect was enhanced by ALDH2 inhibition. Thus, ALDH2 may protect hearts against I/R injury by suppressing PINK1/Parkin-dependent mitophagy.